1991 and networked interoperability - Christensen-Dalsgaard, Birte (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2017)
1991, the year of the first call in the Libraries Programme, was a very different time; the network infrastructure was being built, computers were becoming more powerful, and the information society was being formed based on different technological solutions. Standards (SR, Z39.50, HTML, MP3) and protocols (TCP/IP, OSI) as to how bits should be transported and interpreted, how programs on computers should communicate and how one could find the relevant information (WAIS, Gopher, WWW) were being developed, tested and deployed. Questions were asked that pushed boundaries, experiments were conducted, which delivered new possibilities, and progress on standardization was made. Much happened in the 1990s in a short time span.